Effectiveness Of Sandbag Breathing Exercises In Mechanical Neck Pain - Mansha Muneeb, Balolkhan; Varadhrajulu, G. (Journal of Neonatal Surgery, 2025)
Background: One of the most prevalent musculoskeletal disorders in the general population is chronic neck discomfort. It significantly affects a person's physical, social, and psychological well-being as well as the general standard of living of society. Chronic neck pain can be treated in several ways such as medications and exercises. The aim of this research is to check the effectiveness of sandbag breathing exercises in mechanical neck pain. Objectives: Objectives are to investigate the effectiveness of sandbag breathing exercises in reducing pain and improving functional ability in patients with mechanical neck pain and to assess the impact of sandbag breathing exercises on cervical range of motion, strength and endurance in patients with mechanical neck pain. Methods: This is a randomized controlled trial conducted on mechanical neck pain, 60 subjects who were divided into two groups; experimental and control. Results: Results indicated that therapy was statistically significant in the outcome measures: Numerical Pain Rating Scale (1.43 and 4.96) and Neck Disability Index (14.33 and 21.46) for experimental and control group respectively. Conclusion: The Sand Bag Breathing Technique significantly improved the parameters associated with mechanical neck pain, indicating that it could be employed as a treatment program for neck pain sufferers